Prescription of analgesics in orthopaedic outpatient department at a tertiary health care facility (Mediscope, 2017)
The objective of the present prospective cross sectional descriptive study was to evaluate the prescribing pattern of analgesic drug by orthopaedic surgeons in outdoor patients. This study was conducted in the orthopaedic outpatient department (OPD) of the Department of Orthopaedics, Border Guard Hospital, Pilkhana, Dhaka for six months period from January 2016 to June 2016. Randomly selected 324 prescriptions were collected from the attending patients on OPD and analyzed. The details of prescribed drugs, various analgesics, monotherapy or combined therapy and use of generic name were analyzed. Among the 324 study prescriptions, males and females were 63.9% and 36.1%, respectively. Majority of patients (80.8%) were within 31-60 years of age. Different classes of drugs were prescribed: non-selective non-steroidal anti-inflammatory drugs (NSAIDs) use was 45.2%, selective NSAIDs 2.9%, opioid analgesics 7.3%, H2 blockers 13.6%, proton pump inhibitors 17.1%, muscle relaxants 4.0%, benzodiazepines 8.1%, and other adjuvants 1.9%. Among individual analgesics: diclofenac 23.5%, aceclofenac 6.0%, ketorolac 6.9%, naproxane 10.8%, ibuprofen 3.7%, indomethacin 3.5%, etoricoxib 6.2%, tramadol 15.4% and paracetamol 24.0% were used. Of the 324 patients, 33.6% received combination of analgesics: diclofenac+paracetamol 37.6%, aceclofenac+paracetamol 14.7%, ketorolac+ paracetamol 20.2%, tramadol+paracetamol 22.9% and diclofenac+tramadol 4.6%. Use of trade names was for 80.5% drugs and generic names for 19.5% drugs. NSAIDs were widely prescribed drugs. Use of selective was less comparing to non-selective NSAIDs. Tramadol was the most commonly prescribed opioid drug. Gastro protective agents were used with NSAIDs. Prescribers need to be encouraged to prescribe drugs only using generic names.Mediscope Vol. 4, No. 1: Jan 2017, Page 11-17